2013
DOI: 10.1038/leu.2013.373
|View full text |Cite
|
Sign up to set email alerts
|

GATA1s induces hyperproliferation of eosinophil precursors in Down syndrome transient leukemia

Abstract: Transient leukemia (TL) is evident in 5–10% of all neonates with Down syndrome (DS) and associated with N-terminal truncating GATA1-mutations (GATA1s). Here we report that TL cell clones generate abundant eosinophils in a substantial fraction of patients. Sorted eosinophils from patients with TL and eosinophilia carried the same GATA1s-mutation as sorted TL-blasts, consistent with their clonal origin. TL-blasts exhibited a genetic program characteristic of eosinophils and differentiated along the eosinophil li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 60 publications
3
37
0
Order By: Relevance
“…The typical morphologic features of blasts are similar to those of AMKL, but the morphology of TAM blasts is variable in practice. Increased neutrophils, myelocytes, monocytes, and basophils are frequently observed in peripheral blood smears, and, interestingly, there are cases of TAM involving prominent eosinophilia . Relatively small percentages of blasts are found in the bone marrow of patients with TAM .…”
Section: Clinical and Hematological Features Of Tammentioning
confidence: 99%
“…The typical morphologic features of blasts are similar to those of AMKL, but the morphology of TAM blasts is variable in practice. Increased neutrophils, myelocytes, monocytes, and basophils are frequently observed in peripheral blood smears, and, interestingly, there are cases of TAM involving prominent eosinophilia . Relatively small percentages of blasts are found in the bone marrow of patients with TAM .…”
Section: Clinical and Hematological Features Of Tammentioning
confidence: 99%
“…These results are especially encouraging, as some HDAC inhibitors are already US FDA approved (e.g., vorinostat) and more are currently in late-stage clinical trials/under review by the FDA (e.g., panobinostat). Similarly, it has been shown that BRD4 inhibition with JQ1 can decrease MYC expression and decrease GATA1s-induced hyperproliferation [80]. As more therapeutic options for targeting epigenetic processes emerge, they will likely present exciting new options for the treatment of ML-DS.…”
Section: Five-year Viewmentioning
confidence: 99%
“…51 This defect was accompanied by impaired Myc gene repression and an expansion in eosinophils. Thus, the regulation of GATA1 chromatin binding and transcriptional activity is controlled by the N-terminus in multiple hematopoietic cells.…”
Section: A D E F B Cmentioning
confidence: 99%